Overview of the current research status of new energy aviation engines - LIU Xiang; ZHU Hongjie; ZHANG Ailing; WEI Hongsen; LIU Wenqi; WAN Hengcheng (Hangkong gongcheng jinzhan, 2025)
In recent years, China′s economy has continued to grow, and the demand for clean energy has become increasingly urgent. The aviation industry has also been actively exploring clean and low emission energy technologies. The use of new fuels and new energy for new aviation engines is considered an important solution to reduce carbon emissions. This article provides an overview of the research status of new energy aviation engines. Firstly,the development history of aviation engines is introduced in chronological order. Then, the research status of new fuel aviation engines, electric aircraft, fuel cell aviation engines, etc. is introduced. Finally, the future research of new energy aviation engines is discussed.